The Contribution of Madrasah Culture to Character Formation and Soft Skill Development of Students at MTs Pamulangan Sleman - Ahmad Ali Ath Har ali (Insight School Academy, 2025)
Introduction to The Problem: Education in the 21st century emphasizes not only the mastery of academic competence but also the non-academic abilities that support students' success in social and professional life. These abilities are known as soft skills, which encompass interpersonal and intrapersonal skills. As an Islamic educational institution, the madrasah has great potential to develop both types of skills through a madrasah culture that is applied in a sustained manner.Purpose: This study aims to analyze the contribution of madrasah culture to the character formation and soft skill development of students within the context of MTs Pamulangan Sleman. Design/methods/approach: This study uses a literature review (library research) method by examining various national journals, international journals, books, and scientific articles obtained through Google Scholar. Findings: The results of the review show that madrasah culture, realized through religious habituation, the exemplary conduct of teachers, the enforcement of discipline, social activities, and collaborative learning activities, makes a significant contribution to the development of students' religious character, responsibility, discipline, communication skills, cooperation, self-control, and self-awareness. In addition, a madrasah culture applied consistently is able to create an educational environment that supports students' social and emotional development. This study demonstrates that madrasah culture can serve as a strategic instrument for shaping character while developing students' soft skills in a sustainable manner.